2017
DOI: 10.5152/tud.2017.01033
|View full text |Cite
|
Sign up to set email alerts
|

Update on the novel management and future paternity situation in adolescents with varicocele

Abstract: Varicocele is a progressive disease, and the incidence of varicocele and varicocele related testicular hypotrophy increases with puberty. This review updates novel management and future paternity potential in adolescents with varicocele. Main goal of treatment of the adolescent varicoceles is preservation of fertility. Current recommendations for adolescent varicocele repair are testicular hypotrophy (>2 mL or >20%) on the affected side and/or impaired spermatogenesis in the post-pubertal period. The best trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Primary varicoceles in adults and adolescents have been treated with open surgical via macroscopic or microscopic approach, laparoscopic and radiologic intervention via embolisation or sclerotherapy (Çayan & Akbay, ; Çayan et al, , ; Rotker & Sigman, ). Our previous meta‐analysis, consisting of 36 studies, has reported overall spontaneous pregnancy rate as 37.7% with the high inguinal technique, 42% with the microsurgical varicocelectomy, 30% with the laparoscopic varicocelectomy, 33.2% with the radiologic embolisation and 36% with the macroscopic inguinal varicocelectomy for the treatment of primary varicocele in infertile men (Çayan et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary varicoceles in adults and adolescents have been treated with open surgical via macroscopic or microscopic approach, laparoscopic and radiologic intervention via embolisation or sclerotherapy (Çayan & Akbay, ; Çayan et al, , ; Rotker & Sigman, ). Our previous meta‐analysis, consisting of 36 studies, has reported overall spontaneous pregnancy rate as 37.7% with the high inguinal technique, 42% with the microsurgical varicocelectomy, 30% with the laparoscopic varicocelectomy, 33.2% with the radiologic embolisation and 36% with the macroscopic inguinal varicocelectomy for the treatment of primary varicocele in infertile men (Çayan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence of varicocele may be seen in 0 to 45% of men who underwent primary repair, depending on the original treatment approach (Çayan et al, , ; Rotker & Sigman, ). Recurrence and hydroceles have been reported with higher incidence after repair of paediatric varicoceles (Çayan et al, ; Nees & Glassberg, ). Rotker and Sigman () reviewed varicocele recurrence as an outcome after the treatment, and they reported up to 35% of recurrence, depending on the primary technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varicocele is the most common cause of infertility in the world with high incidence among adults and adolescents (Agarwal et al, 2012; Shefi & Turek, 2006). Epidemiological studies have shown that the onset of varicocele coincides with the onset of puberty (Akbay et al, 2000; Alsaikhan et al, 2016) and also it has a progressive deleterious effect on fertility (Çayan et al, 2017). In fact, due to the high prevalence of varicocele in adolescents, more attention should be directed to this population aiming an early therapy in order to avoid irreparable consequences on the fertility (Abbasi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%